Prevalence of mosquitoes (diptera: culicidae) in and around Bangladesh Agricultural University campus of Mymensingh in Bangladesh - Alam, N; Farjana, T; Khanom, TF; Labony, SS; Islam, KR; Islam, KR; Mondal, MMH (Progressive Agriculture, 2015)
Mosquitoes are the small insects belonging to the order diptera. They are familiar parasitic vectors of a number of transmissible and life menacing diseases. The study was conducted at the Bangladesh Agricultural University (BAU) campus and its surrounding areas in Mymensingh, Bangladesh from January to June, 2013 detect adult mosquito species and their status. Adult mosquitoes were collected using light traps (LTs), insect collecting nets, and human bait (HB) from households, cattle sheds, rice field, botanical garden, dairy farm and poultry farm and staff residential quarters. A total of 2,750 adult mosquitoes were collected from these places. Ten species of mosquitoes under two genera were identified. Among the two genera Culex (84.3%) was the leading group dominated over Anopheles (15.7%) in all areas. In case of Culex species, the most prevalent mosquito species was the Cx. quinquefasciatus (39%) followed by Cx. fuscocephala (23.7%), Cx. tritaeniorhynchus (15.8%), Cx. gelidus (4.0%), Cx. whitmorei (1.2%), Cx. vishnui (0.3%) and Cx. whitei (0.3%). On the other hand, among Anopheles species, An. bengalensis (11.1%) was found in the highest percentage followed by An. vagus (3.8%) and An. jayporiensis (0.8%). Among the studied areas, the highest prevalence of mosquitoes were collected from cattle sheds (40.7%), followed by households of Balashpur (16.2%), Boyra (14.9%) and Kewatkhali (12.4%). Though Culex species was found as dominant species in all areas, the highest percentage (96.7%) was found in staff residential area in BAU campus, whereas, the highest prevalence of Anopheles species (28.7%) was found in cattle shed. We found that two genera were prevalent together in almost all areas, however, though Culex was the dominant one. In conclusion, our survey provided useful information on the prevalence of mosquito species regarding the distribution and diseases control. Progressive Agriculture 26:60-66, 2015